2016
DOI: 10.7151/dmgt.1857
|View full text |Cite
|
Sign up to set email alerts
|

A maximum resonant set of polyomino graphs

Abstract: A polyomino graph H is a connected finite subgraph of the infinite plane grid such that each finite face is surrounded by a regular square of side length one and each edge belongs to at least one square. In this paper, we show that if K is a maximum resonant set of H, then H − K has a unique perfect matching. We further prove that the maximum forcing number of a polyomino graph is equal to its Clar number. Based on this result, we have that the maximum forcing number of a polyomino graph can be computed in pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…For hexagonal systems, Xu et al [34] proved that the maximum forcing number is equal to its resonant number. For polyomino graphs [18,39] and BN-fullerene graphs [26], the same result also holds. For more researches on the minimum and maximum forcing numbers, see [10,16,28,29,31,33,[35][36][37][38].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…For hexagonal systems, Xu et al [34] proved that the maximum forcing number is equal to its resonant number. For polyomino graphs [18,39] and BN-fullerene graphs [26], the same result also holds. For more researches on the minimum and maximum forcing numbers, see [10,16,28,29,31,33,[35][36][37][38].…”
Section: Introductionsupporting
confidence: 54%
“…For general 2-connected plane bipartite graphs, Abeledo and Atkinson [1] obtained that the resonant number can be computed in polynomial time. Hence the maximum forcing numbers of hexagonal systems [34], polyomino graphs [39] and BN-fullerene graphs [26] can be computed in polynomial time.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…For a hexagonal system with a perfect matching, Xu et al [22] showed that the maximum forcing number is equal to the Clar number, which can measure the stability of benzenoid hydrocarbons. Also, some similar results can be found in polyomino graphs [25] and (4,6)-fullerene graphs [15]. Furthermore, the maximum forcing numbers of some product graphs have been studied, such as rectangle grids P m × P n [2], cylindrical grids P m × C n [2,9], and tori C 2m × C 2n [11].…”
Section: Introductionmentioning
confidence: 69%
“…For the maximum forcing number of Q n , Alon proved that for sufficiently large n this number is near to the total number of edges in a perfect matching of Q n (see Riddle (2002)), but its specific value is still unknown. Afterwards, Adams et al (2004) generalized Alon's result to a k-regular bipartite graph and for a hexagonal system, a polyomino graph or a (4, 6)fullerene, Xu et al (2013); Zhang and Zhou (2016); Shi et al (2017) showed that its maximum forcing number equals its Clar number, respectivey. For a graph G with a perfect matching, Lei et al (2016) connected the anti-forcing number and forcing number of a perfect matching of G, and showed that the maximum forcing number of G is no more than Af (G).…”
Section: Introductionmentioning
confidence: 96%